A study on the technical and financial feasibility of producing lactic acid from sugarcane and beet molasses - Nahla M. Salatein; Ahmed F. Omara; Aziz R. Mansour; Irene S. Fahim (Results in Engineering)
Lactic acid (LA) can be produced through fermentation by various microorganisms using various biological feedstocks. The present study conducted an estimation of the necessary resources, including equipment, raw materials, energy, and labour, as well as the associated costs, to produce LA through a yeast-based fermentation route. The techno-economic feasibility of establishing a pilot plant with a production capacity of 50 litters/ day (18 tons / year) within a plastic factory was assessed. The initial investment for setting up the pilot plant was approximately 400,000 EGP. The cost/kg of LA saw a decrease from 67.48 to 25.13 EGP over the trimesters, indicating potential economies of scale and operational efficiencies as production expanded. Revenue projections showed a gradual and consistent increase, starting at 288,283 EGP in Year 1 and steadily climbing to 1,688,721 EGP by Year 10, indicating a robust and promising revenue stream over the projected period. A cradle-to gate LCA was performed using Open LCA software, The impact evaluation for lactic acid manufacturing shows considerable environmental impacts across affect categories. The influence 2002+ approach measured water acidification at 13.828 kg SO₂ equivalent, indicating significant influence on aquatic ecosystem acidity. At 4.942 kg TEG soil, terrestrial ecotoxicity was substantially higher than aquatic ecotoxicity at 8.57 kg TEG soil, suggesting potential harm to terrestrial biodiversity. The CML-IA baseline approach showed nutrient enrichment with 7.473 kg PO₄ eq acidification potential and 5.3 kg SO₂ eq eutrophication impact.